DIFFERENCES IN VAULT RUN-UP VELOCITY IN ELITE GYMNASTS - Lucija Milčić; Kamenka Živčić; Tomislav Krističević (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
The aim of this study was to compare differences in run-up velocity between Handsprings, Tsukahara and Yurchenko entry on vault. A sample consisted of 48 jumps performed on vault, 19 Handsprings, 17 Tsukahara and 12 Yurchenko entry on vault. Data were collected on a World Cup competition held in Osijek, 2017. Run-up velocity was measured by speed radar gun (Stalker ATS, S PRO II). Descriptive statistic was calculated for all variables and differences in run-up velocity were determined by one-way ANOVA and Bonferroni post-hoc test at the level of statistical significance at p<.05. Average run-up velocity at Handspring entry was 8,06 m/s, Tsukahara, 8,06 m/s and Yurchenko entry on vault table was 7,66 m/s. ANOVA showed that exist statistical significant differences in run-up velocity between handspring and Yurchenko and between Tsukahara and Yurchenko entry. The results of this study indicated that different entry on vault table has different run-up velocity, which will help coaches and scientists to improve the vault technique.